Breaking the Ban? The Heterogeneous Impact of US Contestation of the Torture Norm. Issue 1 (20th February 2019) - Schmidt, Averell; Sikkink, Kathryn
Abstract: Following the attacks of 9/11, the United States adopted a policy of torturing suspected terrorists and reinterpreted its legal obligations so that it could argue that this policy was lawful. This article investigates the impact of these actions by the United States on the global norm against torture. After conceptualizing how the United States contested the norm against torture, the article explores how US actions impacted the norm across four dimensions of robustness: concordance with the norm, third-party reactions to norm violations, compliance, and implementation. This analysis reveals a heterogeneous impact of US contestation: while US policies did not impact global human rights trends, it did shape the behavior of states that aided and abetted US torture policies, especially those lacking strong domestic legal structures. The article sheds light on the circumstances under which powerful states can shape the robustness of global norms.